2017
DOI: 10.4040/jkan.2017.47.4.551
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Predicting Career Satisfaction of Nurses Experiencing Rotation

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution NoDerivs License. (http://creativecommons.org/licenses/by-nd/4.0)If the original work is properly cited and retained without any modification or reproduction, it can be used and re-distributed in any format and medium. Purpose: This study aimed to present and test a structural model for describing and predicting the factors affecting subjective career satisfaction of nurses experiencing rotation and to develop human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…Job rotation causes various difficulties due to the challenges of the tasks in a new department, issues with adapting to new personal relationships, and changes in daily life (Huang et al ., ). It not only accompanies a lack of a sense of belonging and the burden of having to learn new tasks (Ortega, ), but is also believed to be a hindrance stress for hospital nurses because most job rotations are implemented unilaterally as a means of coordinating administrative tasks by the hospital regardless of the nurse's wishes (Shin & Yu, ). The results of the study are similar to those of Kang (), who analyzed job‐related stress and self‐efficacy, including job rotation of hospital nurses, and found that self‐efficacy decreases with greater job‐related stress.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Job rotation causes various difficulties due to the challenges of the tasks in a new department, issues with adapting to new personal relationships, and changes in daily life (Huang et al ., ). It not only accompanies a lack of a sense of belonging and the burden of having to learn new tasks (Ortega, ), but is also believed to be a hindrance stress for hospital nurses because most job rotations are implemented unilaterally as a means of coordinating administrative tasks by the hospital regardless of the nurse's wishes (Shin & Yu, ). The results of the study are similar to those of Kang (), who analyzed job‐related stress and self‐efficacy, including job rotation of hospital nurses, and found that self‐efficacy decreases with greater job‐related stress.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, if effective management and coping with job rotation stress is seen as an important aspect of an individual's stress appraisal or management of psychological coping resources, job rotation must be implemented in consideration of both the wishes of the nurses themselves and their competence or expertise. Furthermore, it should be implemented through fair methods and clear procedures (Shin & Yu, ) that ensure it is not used as a means of punishment or to exert pressure to resign. There must also be a support system, such as random rotation prevention after maternity leave or leave for infant care, including a preliminary survey of preferences or a guarantee of a standby period for job rotation so that nurses can adjust to the tasks demanded by their new department through training and various forms of support for adjustment to a new department.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations